The Influence of Entrepreneurial Characteristics On The Success of The Service Business At Elfa Music School Bandung - Deasy Sandya (RIGGS: Journal of Artificial Intelligence and Digital Business, 2023)
The lack of jobs in Indonesia at this time requires every individual to have the ability to be an entrepreneur in order to survive. One of the entrepreneurial endeavors that are widely practiced today is the creative industry. At this time, the creative industry is very necessary. Moreover, the creative industry is an industry with renewable sources because it focuses on creation. In contrast to industries in the mining and oil and gas sectors which will increasingly run out. The business that is being pioneered now, namely the music course/school business, which is one form of business engaged in the service sector and is expected to become the driving force of the Indonesian economy. To overcome the problems of lack of management skills in business management, limited capital, marketing networks, human resources, and technology/techniques used and realize the success of a music course/school business, of course, real efforts are needed from the entrepreneur. The type of research used is descriptive and verification with descriptive survey and explanatory survey research methods. Data were obtained through questionnaires, interviews, and observations in the field. The results of data collection with primary data sources obtained a sample size of 46 respondents. The analysis method used is path analysis. The results showed that the effect of entrepreneurial characteristics on the success of the Elfa Music School Antapani Bandung service business was 94.8%. The greatest influence is on the leadership-oriented sub-variable, while the smallest influence is on the future-oriented sub-variable.